Gender and the South African labour market: Policy relevant research possibilities using South African tax data - Amina Ebrahim; Kezia Lilenstein (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper has three primary objectives. First, it provides a broad overview of the available South African data used to examine gender in the labour market, with specific reference to the South African Revenue Services (SARS) tax data which has recently been made available. Second, the paper provides a brief overview of the existing South African literature, with a focus on the gender dynamics of the labour market. Last, this paper identifies the areas in which the availability of the SARS data has made new research possible, specifically in the gender dynamics of the South African labour market. We identify six key research areas that can immediately be undertaken using the tax data.
Keywords: J01; E24; 330; administrative data; employment; gender; income inequality; wages